Political Education In Realizing Healthy Democracy In Krejengan Village - Mushafi Mushafi; Emi Badriatur Rif’ah; Eka Shanty Fitriyanti; Fitayatul Ilmiah; Isyfina Choirunnisa; Syamsuri Syamsuri; Faqih Rizki.M (Abdimas Paspama, 2023)
This service is about Political Education in Realizing Healthy Democracy in Krejengan Village, Probolinggo Regency. This service was taken as a solution to several problems in the General Election process. This political education will provide village communities with an understanding of the categories of abuse that promote dirty politics and thus harm democracy in Indonesia. Participants in this service previously underwent a Pre-Test and Post-Test.